“A Galaxy of Youth and Beauty”: Beauty Entertainment in Late Victorian Ontario - Harker, Sydney (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2022)
In late nineteenth-century Ontario, beauty contests and shows were forms of entertainment influenced in part by shifting cultural trends in entertainment and newspaper reports from outside of Canada. While commercialized beauty shows took place in theatres and filled a growing space for leisure entertainment, beauty contests were often held at community events, such as agricultural fairs and association picnics. As practices of inherently sexualized bodily display, they functioned as sites of acceptable public desirability. Late nineteenth-century beauty entertainment capitalized on the heightened visibility of women in public spaces and popular interest in public display in late Victorian Ontario, which, as read through the Ontario press, resulted in an expression of modernity where women’s cultural value was tied to their appearance.